NRBF2 Regulates Mitophagy via Interaction With AMBRA1 to Influence Sepsis-Induced Acute Lung Injury - Shuang Lu; Wenjing Zhao; Yujie Wang; Can Li; Jingzhang Zeng (Discovery Medicine, 2026)
Background: Sepsis-induced acute lung injury (ALI) is a critical clinical challenge with substantial mortality. While mitophagy plays a pivotal role in ALI pathogenesis, the mechanisms underlying the involvement of nuclear receptor binding factor 2 (NRBF2), a key regulator of autophagy, in this process remain unexplored. Therefore, this study investigated whether NRBF2 regulates mitophagy by interacting with autophagy and beclin 1 regulator 1 (AMBRA1), thus influencing the progression of sepsis-induced ALI. Methods: The cecal ligation and puncture mouse sepsis model and lipopolysaccharide (LPS)-induced endothelial cell model of ALI were used. NRBF2 expression was inhibited using lentiviral interference, and molecular biology and bioinformatics analyses were performed to investigate the effect of NRBF2 on mitophagy and ALI. The STRING database was used to predict the NRBF2–AMBRA1 interaction, which was subsequently validated using NRBF2 mutants with specific domain deletions. Results: NRBF2 expression was significantly upregulated in septic ALI models (p < 0.001). In vitro, NRBF2 knockdown suppressed excessive LPS-induced mitophagy activation, improved mitochondrial function, and reduced the release of inflammatory factors (p < 0.05). In addition, the autophagy inhibitor chloroquine and mitochondrial division inhibitor 1 reversed mitochondrial dysfunction caused by NRBF2 overexpression (p < 0.01). In vivo experiments further confirmed that NRBF2 knockdown alleviated the pathological progression of sepsis-induced ALI (p < 0.05). Mechanistically, NRBF2 regulated mitophagy by interacting with AMBRA1 via its microtubule-interacting and trafficking domain (p < 0.05). Conclusion: Our findings establish that NRBF2 exacerbates sepsis-induced ALI by promoting AMBRA1-dependent mitophagy, highlighting NRBF2 as a potential therapeutic target.